PENGARUH EXPERIENTIAL MARKETING DAN CITRA PERUSAHAAN TERHADAP WORD OF MOUTH (WOM) - Setiawati, Esust; Rozinah, Siti (Premium Insurance Business Journal, 2020)
This study examines the impact of experiential marketing and image on word of mouth (WOM). The methode used explanatory survey with random sampling. The respondent in this study were 100 respondent. The data were analyzed using linier regression. The result showed experiential marketing don’t have significant on word of mouth and image variabels has significant on word of mouth. The both of variables have simultan on word of mouth.